Resume of the popular memory on two schools that have existed in Tamandaré/PE / Resgate da memória popular sobre duas escolas que existiram em Tamandaré/PE - Maria do Carmo Ferrão Santos (Diversitas Journal, 2019)
This work aims to rescue the memories kept in the memory of the natives and former residents of Tamandaré, about the existence of two federal institutions that functioned here: the Board of Trustees João Coimbra (1924 to 1941) and the School of Fisheries of Tamandaré (1954 to 1975). Memory is one of the foundations that gives meaning to the past events of life. Through informal conversations, it was possible to perceive that the local population preserved the events related only to the second school, claiming that only this one was positively marked, which made it remarkable in the individual and collective memory of the population of Tamandaré.